Quality of life and attitudes toward sexuality: Study of older adults living in Quito - Salinas Paucar, Karen (2025)
Sexuality in old age continues to be a little-discussed topic, despite its impact on overall well-being. Exploring this relationship allows us to broaden our understanding of quality of life at this stage of life. The objective of the research was to examine the relationship between quality of life and attitudes toward sexuality in older adults in Quito, also taking into account sociodemographic variables such as age, sex, the presence of a stable partner, and educational level. The study was conducted using a quantitative approach, with a non-experimental, cross-sectional, descriptive-correlational design. The sample consisted of 100 older adults selected through intentional non-probabilistic sampling, who completed the WHOQOL-OLD and CASV questionnaires. The findings showed a significant negative correlation of -0.475 between quality of life and attitudes toward sexuality, reflecting that more conservative attitudes toward sexuality are associated with a lower perception of well-being. Similarly, variables such as age and educational level had an impact on specific dimensions, such as autonomy and intimacy. In conclusion, restrictive attitudes toward sexuality can adversely affect quality of life in old age. These results highlight the need to promote educational and awareness-raising spaces that encourage a stigma-free experience of sexuality in older adulthood.